A palavra como processo reflexivo: a poesia da invencionice de Manoel de Barros - Moncinhatto, Maria Adriana Silva (2009)
This research work aims to show the word as creative process in the trilogy Memórias Inventadas, work of the poet Manoel de Barros, which includes the following books: A Infância (2007), A Segunda Infância (2008), A Terceira Infância (2009). For this, we try to understand how the poet makes use of the metapoetry and wit, understood here as compositive elements that expose to the reader the do poetic in its most original and creative form. We introduce the concept of metalanguage from authors Haroldo de Campos, Samira Chalhub and João Alexandre Barbosa, establishing relations between the metalanguage and the poetic work of Manoel de Barros. If in the concept of wit, we work with Sigmund Freud s theories, about the wit as sparkly unconsciousness and André Jolles, for whom the wit can be considered a so-called "simple forms." For this search, we focus on the picture of the child be and/or little boy and the images of "things from the ground" to put in evidence the do poetic that appropriates of the organic element to turn it into, metalinguistically, material of poetry. We also observe how Manoel de Barros puts in check the common place and works with the most unusual the creation of a trans-world from the metaphorization and said of mind, revised as graces, responsible for the wit effect in the poems. Finally, we analyze the barreana s poetic construction through the perspective of the invention or reinvention, once the reader merges in a constantly recreated and highly imagery world that invites him to join their misplaced